3-Hydroxytyrosol as a phenolic cholinesterase inhibitor with antiamnesic activity: a multimethodological study of selected plant phenolics - Ucar Akyurek, Tugba; Senol Deniz, F. Sezer; Suntar, Ipek; Eren, Gokcen; Ulutas, Onur Kenan; Orhan, Ilkay Erdogan (Frontiers in Pharmacology, 2025)
BackgroundPlant phenolics are increasingly being investigated for their diverse biological activities, including neuroprotective effects relevant to conditions like Alzheimer’s disease.ObjectiveThe neurobiological potential of 37 plant phenolics was screened through a multifaceted approach encompassing in vitro enzyme inhibition and antioxidant assays, in vivo antiamnesic evaluation, and in silico molecular docking and toxicity predictions.MethodsThe compounds were tested for their cholinesterase (ChE) inhibition potentials, metal-chelation activities, and copper-reducing antioxidant capacities (CUPRACs) using a microtiter assay as well as ferric-reducing antioxidant power assays. Additionally, the in silico ADME, pharmacokinetic, and toxicokinetic profiles of the compounds were predicted using computational platforms.ResultsSeveral compounds exhibited significant inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activities. Of these, quercetin was found to be the most active inhibitor, with IC50 values of 1.22 ± 0.79 mM against AChE and 2.51 ± 0.04 mM against BChE. Some of the other compounds, including caffeic acid (IC50: 3.51 ± 0.62 mM), apigenin (IC50: 3.52 ± 0.08 mM), and taxifolin (IC50: 7.18 ± 2.05 mM), also showed AChE inhibition. Then, oleuropein, rosmarinic acid, gallic acid, epigallocatechin gallate, and 3-hydroxytyrosol were further investigated for their antiamnesic activities using a passive avoidance test in scopolamine-induced mice; our data showed that these compounds were effective considering the latency time of the mice and that 3-hydroxytyrosol showed the highest antiamnesic effect. The dual inhibitory compounds were subjected to molecular docking experiments with ChEs, and the in silico toxicities of three compounds were assessed using the PASS and SwissADME prediction programs.ConclusionOur data provide compelling evidence for the neuroprotective potentials of several plant phenolics. Notably, 3-hydroxytyrosol was identified for the first time as a ChE inhibitor with significant in vivo antiamnesic activity and warrants further investigation.